Population-based incidence rates and increased risk of EGFR mutated non-small cell lung cancer in Māori and Pacifica in New Zealand - Aye, Phyu Sin (PLoS One, 2021)
BACKGROUND: Non-squamous non-small cell lung cancer (NSCLC) patients with Epidermal Growth Factor Receptor (EGFR) mutation benefit from targeted treatments. Previous studies reported EGFR mutation-positive proportions among tested non-squamous NSCLC patients. However, incidence rates and population risk of EGFR mutation-positive and EGFR mutation-negative non-squamous NSCLC have not been assessed. This study therefore aimed to estimate the population-based incidence rates of EGFR mutation-positive and EGFR mutation-negative non-squamous NSCLC in different population groups defined by sex, ethnic group and smoking status. METHODS: This study included data from all non-squamous NSCLC patients diagnosed in northern New Zealand between 1/02/2010 and 31/07/2017 (N = 3815), obtained from a population-based cancer registry. Age-specific incidence rates, WHO age-standardised rates (ASRs) and rates adjusted for incomplete testing were calculated for EGFR mutation-positive and EGFR mutation-negative diseases for the study cohort as a whole and subgroups of patients. RESULTS: Among 3815 patients, 45% were tested for EGFR mutations; 22.5% of those tested were EGFR mutation-positive. The ASR of EGFR mutation-positive NSCLC was 5.05 (95%CI 4.71–5.39) per 100,000 person-years. ASRs for EGFR mutation-positive NSCLC were higher for females than males: standardised incidence ratio (SIR) 1.50 (1.31–1.73); higher for Pacifica, Asians and Māori compared with New Zealand Europeans: SIRs 3.47 (2.48–4.85), 3.35 (2.62–4.28), and 2.02 (1.43–2.87), respectively; and, only slightly increased in ever-smokers compared with never-smokers: SIR 1.25 (1.02–1.53). In contrast, the ASR of EGFR mutation-negative NSCLC was 17.39 (16.75–18.02) per 100,000 person-years, showing a strong association with smoking; was higher for men; highest for Māori, followed by Pacifica and then New Zealand Europeans, and lowest for Asians. When corrected for incomplete testing, SIRs by sex, ethnicity and smoking, for both diseases, remained similar to those based on tested patients. CONCLUSION: The population risk of EGFR mutation-positive NSCLC was significantly higher for Māori and Pacifica compared with New Zealand Europeans.